A survey of research in public administration, 1980-1990 - Pai Panandiker, V. A., 1935-; Indian Council of Social Science Research (Delhi : Konark, 1997)
Contributed articles.
Includes bibliographical references and index.
Keywords: Public administration -- India; India -- Politics and government -- 1977-